Public Perception and Obedience with Social Distancing Policies during the COVID-19 Pandemic in Jakarta, Indonesia - Widyamurti, Widyamurti; Sitorus, Edwina Bernita; Susanna, Dewi; Wispriyono, Bambang; Kusuma, Aria; Mahkota, Renti (Kesmas, 2022)
The Indonesian Government established a social distancing policy to prevent COVID-19 transmission. However, this implementation will be ineffective without the compliance of the people. This study aimed to analyze the relationship between public perception and obedience with social distancing in terms of the variables based on the Health Belief Model. This study used a cross-sectional design with a population of Daerah Khusus Ibukota (DKI) Jakarta’s indigenes within the productive age of 15-64 years. The sample comprised 408 participants, with the independent variables of sociodemographics (age, gender, occupation, and education) and health beliefs (perceived susceptibility, severity, benefits, barriers, and self-efficacy). Meanwhile, obedience to social distancing was the dependent variable. Data were obtained through an online questionnaire and evaluated with the bivariate and multivariate analysis using Chi-square and logistic regression tests. Gender (OR = 2.327; 95% CI = 1.404-3.857) and perceived self-efficacy (OR = 2.609; 95% CI = 1.726-3.945) were significantly related to social distancing obedience. Meanwhile, no statistical correlation (p-value>0.05) was found with sociodemographics, perceived susceptibility, severity, benefits, and barriers. The males with low self-efficacy were more likely to disobey the social distancing policies. The individual’s self-efficacy perception increased with their level of obedience to social distancing policies.